Urmila of Kavita Kane’s Sita’s Sister: A Paradigm of a Contemporary Indian Women - Sharma, Poonam; Bhatnagar, Nitin (The journal of contemporary issues in business and government, 2021)
The epics like the Ramayana and the Mahabharata have always remained the integral part of the Indian cultural tradition. They have been told or retold several times, getting communicated from one generation to another. The Ramayana celebrates the victory of goodness over evil, obedience, call of duty, brotherhood, compassion, sacrifice – all looped into the thread of Indian culture. These issues are depicted mainly through male characters, while most of the females have been kept on the margins. In this very stream is Urmila (Laxmana‟s wife), who has not received the lime light she deserves. Kavita Kane, in her novel Sita‟s Sister, has lifted the Urmila of the traditional versions of the Ramayana, from the periphery and placed her on the centre stage of the fabric. She has reiterated the myth from a daring and unwavering Urmila‟s perspective – a standpoint that is not dissimilar to that of the modern Indian woman. The present paper explores this particular stand of Kane‟s Urmila and studies her proximity from this contemporary angle.